PROFIL KEMAMPUAN NUMERASI PESERTA DIDIK KELAS VIII SMP NEGERI 16 PALU DALAM MENYELESAIKAN SOAL AKM: Profile Of Numeracy Ability Of Class VIII Students Of SMP Negeri 16 Palu In Solving AKM Quetions - Salamah, Ummu; Karniman, Tegoeh S.; Hadjar, Ibnu; M., Bakri (Universitas Tadulako, 2025)
This study aims to describe the numeracy skills of class VIII students of SMP Negeri 16 Palu in solving AKM problems. This research is a descriptive research with qualitative approach. The subjects of this research were students of class VIII SMP Negeri 16 Palu consisting of three people, namely one high ability student, one medium ability student and one low ability student. Data collection techniques used observation, tests, interviews, and documentation. The results of this study indicate that (1) The profile of numeracy skills of high-ability students can meet all indicators of numeracy skills, meaning that the subject is able to master the use of numbers and symbols, as well as the stage of analyzing information and interpreting and mastering it well. (2) The numeracy ability profile of medium ability learners is only able to master two indicators, meaning that the subject masters the use of symbols and evaluates, and cannot draw conclusions from the answers that have been found. (3) The numeracy profile of low ability learners is only able to master the use of symbols and numbers, unable to fulfill the other two indicators.